A Socioeconomic View of Status And Prospects of Goat Farming in Rural Areas of Nepal - Neupane, N; Neupane, H; Dhital, B. (Journal of the Institute of Agriculture and Animal Science, 2018)
As Nepal is agriculture based country, 65% of people are engaged in agriculture Nepal. Moreover, the contribution of livestock to national GDP is significant. In this regard, an attempt has been made to review the prevailing situation of goat farming and various socio economic dynamics related to goat farming in Nepal. Various reports revealed the importance of livestock and furthermore small ruminants have situational advantages in context of rural areas of Nepal where many farmers are poor to afford bigger animals. Moreover, internal and international migration is worsening the availability of male youths which is further explaining the suitability of small ruminants in our context. Goat is the most popular small ruminant which can be handled by women and children in absence of young male members. It not only provides employment to the rural poor, it also acts as a security against the crop failure and has religious importance. Since supply is far behind the demand which is fulfilled through import, sufficient effort is necessary to increase the goat production in order to reduce the import and improve trade deficit of the country.